Synthesis and applications of carbon dots - Nolan, Andrew Steven (The University of Edinburgh, 2015)
The use of non-invasive methods to visualise and monitor processes inside living organisms is vital in the understanding and diagnosis of disease. The work in this thesis details the synthesis and applications of a new imaging modality; carbon dots, whose inherent fluorescence and non-toxic nature makes them attractive alternatives to more traditional ‘quantum dots’. In this thesis, different methods of carbon dot synthesis were attempted in order to produce carbon dots of the desired size and morphology. Nitrogen-containing carbon dots generated from 1,4-addition polymers provided the most successful route with optical and structural characteristics studied by TEM, UV-Vis and fluorescence spectroscopy and XPS. The biological behaviour of the carbon dots produced by this method were also evaluated. The ability of these carbon dots to up-convert when excited at long excitation wavelengths was studied. A number of biologically relevant applications of the carbon dots were studied. Using amine-functionalised carbon dots, cell targeting cargoes were conjugated and the effects of the carbon dot-cargo conjugates on cell lines were studied.
Keywords: carbon dots; optical imaging; fluorescence; cellular imaging